Geoelectrical investigations on coastal aquifers to assess the saline water intrusion in Nghi Son, Thanh Hoa - Vu, Nguyen Trong; Duan, Nguyen Ba; Tung, Tran Dinh (Vietnam Journal of Marine Science and Technology, 2017)
This paper presents the results of geoelectrical investigations for delineation of the aquifers and determination the hydrogeological situation of the water bearing in Nghi Son economic zone. Following the geophysical investigations and the stratification of geological formation, the boundary between fresh and saline water is determined in study area. The geoelectrical measurements indicate that the saline water intrusion within the Pleistocene aquifer occurs along the coastline of the Northeast part of Nghi Son economic zone. The values of formation resistivity below 20 Ωm imply that the water bearing is brackish or saline water. The geophysical results are corresponding to borehole nearby profiles. The geoelectrical methods have proved to be appropriate tools to investigate 2D geological structure in the coastal areas that have low resistivity of subsurface.